CHARACTERIZATION OF SIZE AND SHAPE OF AMMONIUM PERCHLORATE PARTICLE FROM CHINA, SOUTH KOREA, AND INDONESIA AND THEIR INFLUENCES ON PROPERTIES OF PROPELLANT - Hutauruk, Jones; Bura, Romie Oktovianus; Wibowo, Heri Budi (Indonesian Journal of Aerospace, 2020)
The aim of this study is to obtain characteristics of ammonium perchlorate particle that used in Rocket Technology Center (LAPAN). Characterization begin from the determination of particle size distribution with Particle Size Analyzer. The SEM is used to obtain information about the morphology of AP, furthermore, the results are reprocessed using ImageJ software to analyze the shape of AP particle, and the Surface area was obtained by using BET. Characteristic of AP such as particle size, shape, and surface area are important parameters because those are directly related to propellant combustion energy. Ammonium perchlorate was procured from China, South Korea, and Indonesia with a particle size of 200µm From this study, the particle size of APC200, APH200 and API200 was obtained, which are 265 µm, 236 µm, and 242 µm, with particle shape aggregate value of 0,68, 0,38 and 0,33, roundness of 0,57, 0,79,0,63, and surface area of 1,104 m2/g, 5,561 m2/g, and 2,972 m2/g.